Mobile development: learn du’a for early childhood learners - Mohamed Imran Mohamed Ariff; Natasha Irina Khairul Annuar; Ahmad Farid Najmuddin; Ireen Munira Ibrahim; Noreen Izza Arshad; Samsiah Ahmad; Khairulliza Ahmad Salleh (Institute of Advanced Engineering and Science, 2022)
This project stands by acknowledging the use of mobile technology is progressively popular among early childhood learners in recent years. But, an extensive systematic literature search on educational mobile technology and touchscreen indicated that most of the applications are not suitable for early childhood learners as it lacks several multimedia features. Therefore, this project designates the development procedure of an educational mobile application for early childhood learners, who are very receptive to new knowledge and information. As a proof of concept, the development of this application utilizes the learning of the Islamic du’a recitation. This application was designed using the android studio and the flutter software combined with the java programming language. Upon the development of this application, several testings were done and analyzed. The result shows that users were satisfied with the applications as most of the testing scores were highly rated. Based on these results, the usage of this newly mobile application can be suggested to be adopted by early childhood learners.